Vancomycin Intermediate MRSA Isolates Obtained from Retail Chicken Meat and Eggs Collected at Pokhara, Nepal - Devkota, Surya Prasad; Paudel, Ashmita; Gurung, Krishna (Nepal Journal of Biotechnology, 2019)
Antimicrobial resistance among food animal isolates is increasing as a result of their uncontrolled uses. The monitoring of antibiotic resistance among these isolates is very necessary. S aureus was isolated from eggshells and chicken meat samples collected from different retail outlets of the Pokhara metropolitan. Samples were inoculated on Mannitol salt agar aseptically and inoculated overnight. Isolated yellow colonies were further examined by Gram-staining, catalase, and coagulase test to detect S aureus. Methicillin resistance was screened using cefoxitin disc. Vancomycin minimum inhibitory concentration (MIC) of Methicillin-resistant S aureus (MRSA) isolates were determined by the agar dilution method following CLSI guidelines. 139 S aureus were isolated from 205 samples. Among them, 89 were from egg samples (out of 125 samples) and 50 from chicken (out of 80 samples). The overall prevalence of MRSA was 12.94%. Antibiotic resistance was significantly higher in MRSA isolates compared to Methicillin sensitive S aureus (MSSA) isolates. The highest rate of resistance was noted for ampicillin, amoxicillin, and erythromycin while the least resistance was noted for gentamicin and amikacin. Vancomycin minimum inhibitory concentration (MIC) range of the MRSA isolates was 0.25-8μg/ml indicating the detection of both vancomycin-intermediate and sensitive isolates from the samples. This is the first study reporting vancomycin-intermediate S aureus (VISA) isolates from Nepal and indicates the increasing drug resistance among animal isolates. Further surveillance studies about the transmission of these pathogens to humans as well as detail molecular analyses are imminent.